Pengaruh Sales Promotion, Shopping Lifestyle, dan Hedonic Shopping Motivation terhadap Keputusan Impulsive Buying pada konsumen Shopee di Sidoarjo - Fahruddin, Redhi; Yulianto, Mochamad Rizal; Febriansah, Rizky Eka (Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of sales promotion, shopping lifestyle, and hedonic shopping motivation on impulsive buying decisions among Shopee consumers in Sidoarjo. This research uses quantitative methods. The number of samples in this research was 100 respondents. Samples were taken using a non-probability sampling technique with a purposive sampling method. Data analysis in this study used multiple linear regression. The results of this research show that simultaneously and partially the sales promotion, shopping lifestyle and hedonic shopping motivation variables have a significant effect on impulsive buying among Shopee consumers in Sidoarjo.